Proceedings of the Asia Pacific Business and Economics Conference (APBEC 2018) 2019
DOI: 10.2991/apbec-18.2019.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Implementation of IFRS 15 on the Financial Statements of Telecommunication Company (Case Study of PT XYZ)

Abstract: the purpose of this research is to analyze the impact of implementation of IFRS 15 "Revenue from Contract with Customer" on the Financial Statement of Telecommunication Company in Indonesia. The paper presents a qualitative analysis in the form of literature and case study in cellular business process in PT XYZ. This research tries to analyze the magnitude of the impact of implementation on revenue measurement, recognition, presentation, and disclosure processes in the telecommunication company and to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…It was jointly issued by IASB, FASB in May 2014. The FASB version is known as Accounting Standards Codification (ASC) 606 (Bernoully & Sensi Wondabio, 2019). Here's a brief overview of the evolution of IFRS 15 (Mattei & Paoloni, 2018:11) e. Disclosures: Enhanced disclosures are required to provide financial statements to users with more information about the amount, timing, and uncertainty of cash flows and revenue.…”
Section: Evolution and Developmentmentioning
confidence: 99%
“…It was jointly issued by IASB, FASB in May 2014. The FASB version is known as Accounting Standards Codification (ASC) 606 (Bernoully & Sensi Wondabio, 2019). Here's a brief overview of the evolution of IFRS 15 (Mattei & Paoloni, 2018:11) e. Disclosures: Enhanced disclosures are required to provide financial statements to users with more information about the amount, timing, and uncertainty of cash flows and revenue.…”
Section: Evolution and Developmentmentioning
confidence: 99%
“…Hasil penelitian menunjukkan bahwa implementasi IFRS 15 di PT XYZ tidak hanya akan memengaruhi pengakuan pendapatan dan proses persiapan pelaporan keuangan tetapi juga akan berdampak dan memerlukan perubahan pada lingkungan pengendalian internal, sistem informasi dan teknologi, indikator kinerja utama, proses perhitungan imbalan kerja, dan juga hubungan dengan investor. Implementasi IFRS 15 bukan hanya merupakan tanggung jawab bagian akuntansi, tetapi juga memerlukan koordinasi dan kerja tim yang baik antarunit terkait di PT XYZ dalam melakukan perubahan yang diperlukan (Bernoully & Wondabio, 2019).…”
Section: Metode Penelitianunclassified
“…The reported studies by Brink were conducted before the effective date of IFRS 15. Other CCRP-related studies (Amalyan and Amalian, 2015; Bernoully and Wondabio, 2019; Brink, 2013, 2014, 2016; Chapple et al. , 2010; Chun et al.…”
Section: Introductionmentioning
confidence: 99%
“…The reported studies by Brink were conducted before the effective date of IFRS 15. Other CCRPrelated studies (Amalyan and Amalian, 2015;Bernoully and Wondabio, 2019;Brink, 2013Brink, , 2014Brink, , 2016Chapple et al, 2010;Chun et al, 2020;Fourie, 2018;Johansson and Ringius, 2007;Levanti, 2020;Pidduck et al, 2019;Sava, 2014), however also did not include any reference to accounting theory. After the effective date of IFRS 15 no research specifically related to accounting for CCRP transactions could be found.…”
Section: Introductionmentioning
confidence: 99%